Job Satisfaction and Organizational Commitment of Millennial and Gen Z Hotel Employees : A Basis for Management Technique Development - Areola, PhD HSG, Eunice Mareth Querol; Lao, Rochelle Marri P; Javier, Ramoncito P (Journal of Sustainable Community Development (JSCD), 2023)
The workforce is now composed of multi-generational employees. In the coming years, Millennials and Gen Z will dominate the labor force. The purpose of this study is to investigate the job satisfaction and organizational commitment of Millennial and Gen Z hotel employees. Understanding this future hospitality workforce is pivotal as empirical studies since both generations are known to be the “job hopper” generation. There has been a paucity in the study with regards to Gen Z hotel employees as they are still starting to penetrate the workforce. It was also the objective of this study to see whether there is a difference between Millennial and Gen Z employees in terms of their job satisfaction and organizational commitment. This study solely focused on hotel employees in Bacolod City (n = 90). The results of the study suggests Millennial and Gen Z employees are highly satisfied, and highly committed with their workplace despite of what previous studies suggest. However, the study also infers that gender of Gen Z employees shows a significant difference when it comes to job satisfaction. It is also extrapolated that employee’s job satisfaction has a strong positive relationship with their organizational commitment. This supports previous studies implying that job satisfaction is a predictor of organizational commitment.